Pengaruh Cita Rasa, Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan (Studi Pada Mixue Ice Cream & Tea Cabang Caringin Kota Bandung) - Shabrina, Ghina Hami Nur; Sarah, Siti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to determine and analyze how taste, price, service quality affect customer satisfaction at Mixue Ice Cream & Tea Caringin Branch, Bandung City. Level measurement using quantitative methods with descriptive and verification approaches using a questionnaire as a data collection instrument and distributed to 97 respondents who are consumers of Mixue Ice Cream & Tea Caringin Branch, Bandung City. While the results of Descriptive research indicate that Customer Satisfaction (Y), Taste (X1), Price (X2) and Service Quality (X3) are in the “Good” category. Verificationally, the variable Taste (X1) on Customer Satisfaction (Y) has a significant effect. Furthermore, the variable Price (X2) on Customer Satisfaction (Y) has a significant effect. The variable Service Quality (X3) on Customer Satisfaction (Y) has a significant effect. Finally, the variables Taste (X1), Price (X2), Service Quality (X3) on Customer Satisfaction (Y) have a significant effect and the amount of influence is 52.6%.